Epistolary Short Story by M.A. Kuzmina 1907: Demonological Narrative, Libertine Transgression, or Stylization of Adventures in Spirit of Henri de Regnier - G. A. Krichevsky (Научный диалог)
The epistolary short story by M.A. Kuzmin 1907 “From the letters of the maiden Clara Valmont to Rosalia Tutel Mayer”. The “layers” of genres and traditions in the text of the novel are studied in order to establish the compatibility of the epistolary genre with narrative strategies of stylization and parody. It turns out that under the narration about the connection of a supernatural being with a person lies the usual story of manipulation and deception of a young ingenuous girl. Nevertheless, the epistolary form helps to more accurately construct the female image. It is noted that the comic effect arises as a result of doubts that appear about the version of events set forth in the letters of the heroine. It is shown that additional attention to poetic autoquotation in the epistolary short story by M.A. Kuzmin opens up the possibility of clarifying the source, which could be chosen for stylization and parody. In addition, it becomes clear that, contrary to the genre epistolary canon, which brings to the fore the inner world of the characters, the novel M.A. Kuzmin contains elements of the adventure novel genre. It is also suggested that the stylization strategy of M.A. Kuzmin can be compared with the imitative narrative of A. de Regnier, which was admired by Russian symbolists.